Language and literature - Morshed, Abul Kalam Manzur; Cakama, Sugata (Cultural survey of Bangladesh series ;, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; covers the period, 3rd century B.C. to 20th century; includes very briefly non-Bengali literature also.